Clinical features of progressive encephalomyelitis with rigidity and myoclonus: Case Report - Qin, Lixia; Chen, Qihua (Frontiers in Immunology, 2025)
Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a rare neurological disorder characterized by rigidity, painful spasms, hyperekplexia, brainstem involvement, and autonomic dysfunction. In China, limited awareness and delayed antibody testing often hinder early diagnosis. Here, we report four cases of PERM, three of which required intensive care unit (ICU) admission. The clinical and immunological features of these patients were systematically summarized. This case series highlights the characteristic clinical and immunological profiles of PERM and underscores the importance of early recognition and timely intervention, as most patients achieve substantial recovery with immunosuppressive therapy.